Upah, Cuti Melahirkan, dan Jaminan Sosial: Tantangan Keadilan Gender di Tempat Kerja - Sulistya Eviningrum; Mina Marista; Elfara Yulyastia Rizki Ananda (Fakultas Hukum, Universitas Boyolali, 2026)
The issue of gender justice in the workplace remains a serious challenge in industrial relations, particularly concerning the fulfilment of women's labour rights. Three crucial aspects that often cause disparities are wages, maternity leave, and employment social security. This study aims to analyse how the implementation of wage policies, maternity leave, and social security affects the realization of gender justice in the work environment. Although the Indonesian constitution guarantees the right to fair treatment in employment relations, female workers still face structural barriers in the form of wage gaps (gender pay gap) and career vulnerability due to reproductive functions. This study uses a normative legal research method with a statutory approach and a conceptual approach. The research results show that the implementation of the latest regulations, such as Law No. 4 of 2024 on Maternal and Child Welfare (KIA Law), brings a breath of fresh air for the protection of reproductive rights through the extension of maternity leave duration, but on the other hand poses the risk of covert discrimination in employment continuity. In addition, the social security system still requires synchronization to be more inclusive of various women's work models. This study concludes that achieving substantive gender justice necessitates regulatory synchronization, strengthening gender-sensitive inspections, and reforming the burden of proof, alongside shifting the financial responsibility for reproductive rights from employers to the national social security system to eliminate structural discrimination and ensure career continuity for female workers.